Liverworts new to Colombia - S. Robbert Gradstein; Jaime Uribe-M; Jorge Enrique Gil-N; Claudia Morales; Maria A. Negritto (Caldasia)
Based on our ongoing studies of the bryophyte flora of Colombia we report 15 liverwort species new to the country: Archilejeunea nebeliana, Colura calyptrifolia, Dibrachiella auberiana, Fossombronia fernandeziensis, Isopaches bicrenatus, Lejeunea angusta, L. concinnula, L. corynantha, L. galeata, L. pulverulenta, L. serpillifolioides, L. tapajosensis, Leptoscyphus hexagonus, Marchesinia languida and Riccia planobiconvexa. Notes are provided on the distribution, habitat and taxonomic differentiation of the species. Lejeunea cochleata is a new synonym of L. angusta, and Taxilejeunea steyermarkii is a new synonym of Lejeunea pulverulenta. With 730 species recorded, in 40 families, Colombia is probably the richest country in liverworts in tropical America.